Pengaruh Good Governance dan Kualitas Pelayanan Terhadap Kepuasan Pasien di Rumah Sakit HVA Toeloengredjo Pare Kediri - Didik Hadi Santosa; Bewa Dangu Wole; Detriana Imeriet Nenobais (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Good governance for hospitals is the first step that can be taken to be able to follow the rules that change and will always change. Patients as health service users that after the patient uses the services of the hospital, the patient will compare the quality of service expected by the patient with what they actually receive. The purpose of this study is to determine the influence of good governance and hospital service quality on patient satisfaction at HVA Toeloengredjo Pare Kediri Hospital. This study is a quantitative research with data analysis using multiple linear regression. The number of samples used was 32 patients. The results of the study showed that good governance had an effect on patient satisfaction by data analysis obtained a significant value of 0.000 < 0.05 and tcal>ttable, H0 was rejected and H1 was accepted, which means that good governance has a positive and significant influence on patient satisfaction. While the significant value is 0.019 < 0.05 and the tcal>ttable, H0 is rejected and H2 is accepted, which means that the quality of service has a positive and significant influence on patient satisfaction. From the results of data processing, it is known that the significant value is 0.000 < 0.05 and the tcal>ttable, H0 is rejected and H1 is accepted, which means that good governance and service quality have a positive and significant influence on patient satisfaction at HVA Toeloengredjo Pare Kediri Hospital.